2013
DOI: 10.1136/amiajnl-2012-001147
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of clinical laboratory results: an experimental comparison of four visualization techniques

Abstract: ObjectiveTo evaluate how clinical chemistry test results were assessed by volunteers when presented with four different visualization techniques.Materials and methodsA total of 20 medical students reviewed quantitative test results from 4 patients using 4 different visualization techniques in a balanced, crossover experiment. The laboratory data represented relevant patient categories, including simple, emergency, chronic and complex patients. Participants answered questions about trend, overall levels and cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Though there has been mention of the importance for user-centered design when developing patient-facing applications within EHRs [11] (such as patient portals), few studies have managed to carry-out the user-centered design process [12] in its entirety. The majority of studies on patient-centered design have explored patients’ information needs when interpreting their test results and how appropriate informatics tools can improve patient comprehension of health concepts [1314151617]. However, few published studies have attempted to take the next steps to use these information requirements to propose new designs for patient-facing interfaces or tools that promote patients’ comprehension of test results and to test these interfaces with patients [16].…”
Section: Background and Significancementioning
confidence: 99%
“…Though there has been mention of the importance for user-centered design when developing patient-facing applications within EHRs [11] (such as patient portals), few studies have managed to carry-out the user-centered design process [12] in its entirety. The majority of studies on patient-centered design have explored patients’ information needs when interpreting their test results and how appropriate informatics tools can improve patient comprehension of health concepts [1314151617]. However, few published studies have attempted to take the next steps to use these information requirements to propose new designs for patient-facing interfaces or tools that promote patients’ comprehension of test results and to test these interfaces with patients [16].…”
Section: Background and Significancementioning
confidence: 99%
“…In a study done by Torsvik et al [4], it was observed that alternative visualizations of laboratory test reports helped clinicians in few special cases. However, it was also observed that these techniques are not ideal in general scenarios.…”
Section: Introductionmentioning
confidence: 97%
“…Visualization is a function of available diagnostic trends and aesthetics, which requires transposition from one or many data sources, and combines disparate data into a workable presentation [2]. Multigraphs, sparklines or box plots are some approaches, which allow representation of co-varying features while showing normal ranges for test results [3]. In clinical practice, new results from many sources are generated systematically over time, depending on the patient and treatment protocol, and require correct interpretation and follow-up.…”
Section: Introductionmentioning
confidence: 99%